2020
DOI: 10.1146/annurev-polisci-050718-032657
|View full text |Cite
|
Sign up to set email alerts
|

Clientelism's Red Herrings: Dead Ends and New Directions in the Study of Nonprogrammatic Politics

Abstract: Research on clientelism often starts from a shared puzzle: How can clientelism be a viable electoral strategy if voters can renege on their commitments to politicians? The standard solution proposed is that politicians resolve this commitment problem with voters through monitoring and enforcement. But there has been startlingly little evidence of individual-level monitoring and enforcement in the recent literature, and many studies now document the use of clientelism even where politicians are aware that the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 78 publications
1
44
1
5
Order By: Relevance
“…Rather, comparativists have shown that such considerations are part and parcel of everyday clientelist transactions in political systems where scholars and citizens have long argued that the practice is antithetical to democracy. Clientelist politicians often deliver payments to their own core supporters (Diaz-Cayeros et al, 2016; Nichter, 2018), and political machines regularly deliver handouts despite their imperfect ability to monitor how recipients vote (Hicken & Nathan, 2020; Kitschelt & Wilkinson, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather, comparativists have shown that such considerations are part and parcel of everyday clientelist transactions in political systems where scholars and citizens have long argued that the practice is antithetical to democracy. Clientelist politicians often deliver payments to their own core supporters (Diaz-Cayeros et al, 2016; Nichter, 2018), and political machines regularly deliver handouts despite their imperfect ability to monitor how recipients vote (Hicken & Nathan, 2020; Kitschelt & Wilkinson, 2007).…”
Section: Discussionmentioning
confidence: 99%
“… 18. Although many clientelist transactions across the world do not rely on monitoring (Hicken & Nathan, 2020), note that a considerable minority of Americans harbor doubts about ballot secrecy. Gerber et al (2013) find that 25% of US survey respondents did not believe that their votes are kept secret.…”
mentioning
confidence: 99%
“…Van de Walle (2009) provides an expansive historical discussion of why parties are poorly institutionalized across much of the continent, part of a larger argument raising doubt about the applicability of common clientelist theories in Africa. Hicken and Nathan (2020) provide an able summary of broker-based individual or collective monitoring explanations, finding them logically and empirically wanting. Simply put, existing work on Kenya and related areas suggests that clientelism is both rarer and less e↵ective than implied by the literature.…”
Section: Lines and Election Administrationmentioning
confidence: 98%
“…They use numerous instruments aimed at ensuring the victory of an incumbent, on a non-ideological / non-policy basis. The range of their activities includes clientelist exchanges, vote-buying, administrative pressure on voters, and so forth (Stokes et al 2013;Frye, Reuter, and Szakonyi 2019;Hicken and Nathan 2020). Direct mobilization activity takes place at the lower levels, and it is well known that lower authorities and lower-ranking officials are held directly responsible to higher level officials, for the election results in their constituencies (Ross 2007).…”
Section: Elections and Opposition Parties In Authoritarian Regimesmentioning
confidence: 99%